RELIGIOUS HARMONY THROUGH THE AGUSTUSAN THANKSGIVING TRADITION: A CASE STUDY OF SEGARAN VILLAGE, WATES DISTRICT, KEDIRI REGENCY - Aprilia Lestari; Melinda Nur Fara; Nur Aini Rahmaningrum; M Thoriqul Huda (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
Indonesia, a country rich in diverse religions, ethnicities, and cultures, has always prioritised interfaith harmony as one of the key aspects necessary to maintain national unity and cohesion. Harmony is defined as a state of calmness, harmony, and mutual respect. In this context, local wisdom plays a crucial role in preserving diversity, serving as a guiding principle that encourages mutual respect, appreciation, and the cultivation of tolerance within a diverse society. Local traditions, known as "Syukuran Agustusan," are cultural expressions that embody significant religious and social values. This tradition is often carried out as an expression of gratitude for independence and as a way to strengthen relationships between communities. This study uses a qualitative approach to understand the phenomenon of interfaith harmony in depth, comprehensively, and in its natural context. This approach provides an opportunity to describe, interpret, and understand the subjective meaning of the participants' experiences. The research location is Segaran Village, located in Wates Subdistrict, Kediri Regency. Data collection techniques include in-depth interviews with community leaders, religious figures, youth, and residents of various religions to explore their opinions and perspectives; participatory observation to observe social interactions and the atmosphere of togetherness. The research findings indicate that the Agustusan Thanksgiving Tradition in Segaran Village is a communal celebration held every night on 17 August, focusing on expressing gratitude for independence and collective prayers for safety. This tradition effectively promotes interfaith harmony through various means, such as serving as an open platform for interaction among all people, regardless of religious background, enabling them to gather and interact, and ensuring there is no discrimination.